Hypothyroidism in diabetes mellitus patients in Eastern Nepal - Robin Maskey; Dhana Ratna Shakya; Jouslin Kishore Baranwal; Poonam Lavaju; Prahlad Karki; Shyam Krishna Poudel (Indian Journal of Endocrinology and Metabolism, 2015)
Context: The coexistence of diabetes mellitus (DM) with hypothyroidism is a known clinical observation. Aims: To estimate prevalence and co-relate that of hypothyroidism in patients with DM in relation to the age and sex, the lipid profile, body mass index visiting diabetes clinic and inpatients in B. P. Koirala Institute of Health Sciences. Settings and Design: The hospital-based descriptive study. Materials and Methods: Two hundred and seventy-one known or newly detected cases of DM aged more than 15 years were selected randomly from September 2012 to September 2013 and subjected to evaluation for thyroid function - clinically and biochemically and other relevant investigations were done. Statistical Analysis Used: For descriptive statistics mean, standard deviation, percentage, proportion were calculated. For inferential statistics following test were carried out at the level of significant 0.05 where confidence interval is 95%. The statistical operations were done through Statistical Package for the Social Sciences version 10. Results: Of 271 subjects, the prevalence of hypothyroidism (clinical and subclinical) in diabetics was, 4.05% (11/271) with females preponderance, of which 7 (30.4%) were clinically hypothyroid and 4 (17.4%) were subclinical hypothyroid. One (4.3%) patient had subclinical hyperthyroidism. The mean age at diagnosis of type 2 DM was 51-60 years. 8.69% of diabetics with primary hypothyroids were having morbid obesity. High-density lipoprotein among different thyroid status were statistically significant (P = 0.042). Conclusions: Hypothyroidism is not uncommon in diabetes, and we found body mass index, mean triglyceride and cholesterol levels were more in those diabetic patients having coexisting hypothyroidism.